2019
DOI: 10.18805/ijar.b-3631
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bypass fat and mineral supplementation peripartum on plasma profile of steroid hormones PGFM and postpartum fertility in Jaffarabadi buffaloes

Abstract: Advanced pregnant Jaffarabadi buffaloes (n=40) of 2-4 parity selected on an organized farm were divided equally into control (routine farm feeding-RFF) and treatment/nutrients supplementation (RFF + bypass fat @ 150-200 g/h/d and ASMM @ 50 g/h/d) groups and were studied from 6 wks prepartum to 8 wks postpartum for plasma profile of steroid hormones and PGF2a metabolites on days -45, -30, -7, 0, +7, +15, +30, +45 and +60 peripartum as well as for puerperal events and postpartum fertility. Half of the buffaloes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Thus, the conception most likely occurs when cervical mucus is most fluid. The findings of Kumar et al [20]; Sharma et al [21] also indicated higher conception in cows having clear and stringy oestrus mucus than those with thick consistency mucus. The consistency of cervical mucus influences the spermatozoa penetration [22].…”
Section: Consistencymentioning
confidence: 94%
“…Thus, the conception most likely occurs when cervical mucus is most fluid. The findings of Kumar et al [20]; Sharma et al [21] also indicated higher conception in cows having clear and stringy oestrus mucus than those with thick consistency mucus. The consistency of cervical mucus influences the spermatozoa penetration [22].…”
Section: Consistencymentioning
confidence: 94%